Childhood and prison: Analysis of the impact on the fundamental rights of children living with their mothers at the “Establecimiento Penitenciario Mujeres de Chorrillos” (Ex Santa Mónica) - Burgos Juárez, Diana (2020)
This article will analyze the regulatory framework that regulates the coexistence of children with their mothers in the “Establecimiento Penitenciario Mujeres de Chorrillos” (Women of Chorrillos Penitentiary Establishment) from a Constitutional Law perspective. Currently, the Criminal Enforcement Code allows inmates to live in prison with their children under the age of three. The aforementioned establishment, following the requirements of national and international regulations, has implemented in its facilities various social programs of health, education and food to ensure a comprehensive development of the children who are in this establishment. This research aims to balance the positive and negative impact of the application of the regulatory framework, through the aforementioned social programs, in the enjoyment of children’s fundamental rights to the family, health, education and the food. The authors consider that the impact on each right are both positive and negative, with the exception of the right to food, which they believe is fully guaranteed. Finally, the authors conclude by proposing solutions to the negative impact caused by the regulatory deficiency.